Persepsi Layanan Bimbingan dan Konseling Sekolah terhadap Minat Siswa Berkonsultasi - El Rahma, Zakiah Nadya; Kholisna, Titin (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Islam Raden Rahmat Malang, 2021)
The importance of Guidance and Counseling Services in guiding and accompanying students in the process of taking their education. However, many students are still reluctant and hesitant to consult and take advantage of Guidance and Counseling services due to various factors, one of which is the students' own perceptions. The various experiences that students feel, form a perception that underlies students 'attitudes and behavior as a reaction to what they think. The purpose of this study was to determine the relationship between perceptions of guidance and counseling services in schools with students' interest in consulting. This research uses a correlational quantitative approach. The research subjects were students of class VIII and IX Mts Miftahul Huda Turen. The research instrument used is a Likert scale with statistical analysis techniques using the Pearson Correlation formula. The results showed there was a positive relationship between perceptions of guidance and counseling services with the interest in consulting. So it can be concluded the importance of student perceptions in Guidance and Counseling services with student interest in consulting, making the results of this study can be an additional insight for the parties involved in an effort to maximize the role and program of the Guidance and Counseling Service in school.